A new species and a new record of genus Hexacentrus Serville, 1831 (Orthoptera: Tettigoniidae: Hexacentrinae) from India - Farooqi, Mohd Kaleemullah; Usmani, Mohd Kamil (Zootaxa, 2018)
The paper deals with a new record Hexacentrus japonicus Karny, 1907 and a new species Hexacentrus bifurcata sp. nov. from India. Necessary and important illustrations with SEM images of stridulatory file of Hexacentrus japonicus and Hexacentrus bifurcata sp. nov. are provided. A key to the Indian species of Hexacentrus and morphometric ranges of all the species have also been included. Type specimens have been preserved for further investigation in Zoology Department, Aligarh Muslim University (ZDAMU).